Computer literacy basics a comprehensive guide to IC3 - Morrison, Connie; Wells, Dolores J.; Ruffolo, Lisa (Cengage Learning, 2015)
Provides an introduction to computer concepts and skills, which maps to the newest Computing Core Certification (IC3) standards. This book covers Computing Fundamentals, Key Applications, and Living Online - everything your students need to be prepared to pass the IC3 exam, and finish the course as confident computer users.